Linear Response Properties Required to Simulate Vibrational Spectra of Biomolecules in Various Media: (R)-Phenyloxirane (A Comparative Theoretical and Spectroscopic Vibrational Study) - Jalkanen, Karl; Jurgensen, V.; Degtyarenko, I. (Elsevier Inc, 2005)
We here present a combined VA, VCD, Raman and ROA vibrational study of phenyloxirane. We have simulated the vibrational absorption (VA), also called IR, vibrational circular dichroism (VCD), Raman scattering and Raman optical activity (ROA) intensities utilizing the density functional theory (DFT) B3LYP hybrid exchange correlation functional and other exchangecorrelation functionals (PBE, PW91, PBE1) with the 6-31G(d,p), 6-31++G(d,p), cc-pVDZ, aug-cc-pVDZ, cc-pVTZ and augmented correlation consistent polarized valence triple zeta (augcc-pVTZ) basis sets. Previously authors have focused on either the VA and VCD spectra or the Raman and ROA spectra of molecules, since the experimental and theoretical instruments and methods for calculating these quantities are quite distinct. Here we show that the combined analysis gives more information, especially with respect to the electric dipole, magnetic dipole, electric dipole-electric dipole polarizability, electric dipole-electric quadrupole polarizability and electric dipole-magnetic dipole polarizability changes during the various induced transitions. The coupling of vibrational and electronic excitations may be used to aid in understanding the photo induced chemical reactivity observed in many systems. This work is a continuation of our goal to interpret the results of experimental studies on the basis of theoretical results, which can help to understand the structure and function of proteins, other biomolecules and ligands in their native environments. As the physical tools used to observe and study biological processes have evolved, so have the theoretical methods and models to interpret, understand and completely utilize the results of these new measurements. The work on developing methods for modeling amino acids, peptides, proteins and ligands in both the non aqueous (lipid) and aqueous environments has involved, of course, many groups. A review of our contributions to this eld has recently been presented. In addition to interpreting existing and new experimental results, we will discuss structural, energetic, conformational, and vibrational studies on a variety of systems that have been used to test and validate levels of theory, and in addition to suggest modications to existing levels of theory, which can make them even more useful than they currently are.